Risk and Return Analysis of top Crypto Coins - Papakollu, Lohith (The journal of contemporary issues in business and government, 2021)
In this paper, risk and return analysis of the top ten currencies are been presented. How risky are cryptocurrencies, when compared to other forms of investment like stock & commodities,is also been analyzed.An equal-weighted crypto index is taken for the comparisonwith S&P 500, Crude oil, Gold, and Crypto coins. Among the crypto coins, there are some which are highlyrisky and some gave high returns. Proper quantitative& statistical analysis is needed to understand the historical behavior. It is important to study the historical behavior patterns to know the future. Descriptive statistical tools are used to see the patterns and Inferential statistical tools are used to understand the estimation of the association between the variables.